Using a 30-cm Mortar Molding Machine to Increase the Productivity of Pottery Craftmen in Mayong Lor Village, Jepara, Central Java - Putri Purwaningrum, Jayanti; Purbasari, Imaniar; Puspita Rini, Gilang; Fajrie, Nur (KnE Social Sciences, 2022)
As part of the community service program between Muria Kudus University and pottery craftsmen in Mayong Lor Village, Jepara, Central Java, a 30-cm mortar molding machine was provided to the craftsmen with an aim to increase the production of 30-cm diameter mortar – a leading local product in Mayong Village area – as well as a means of educating craftsmen on their product development. This article discusses the 30-cm diameter mortar production process before and after the use of the molding machine and describes the prototype of the 30-cm molding machine. The authors conclude that the 30-cm diameter mortar molding machine can help craftsmen to ease the mortar production. The production of mortar per day increases after using the molding machine. Keywords: mortar molding machine, pottery craftsmen, productivity